Function and Aesthetic Value: an Analysis of the Milwaukee Public Museum's Thai Royal Silver Collection - (:unkn) unknown (My University, 2022)
This thesis analyzes 45 objects from the Thai Royal Silver collection currently housed at the Milwaukee Public Museum (MPM). Of these, 41 were donated by a single donor, Dr. Louis Schapiro, who collected the objects during his time working as Medical Advisor for the King of Siam in 1931-1932. Following his death, his son Mark held onto the objects until 1969, when they became a part of the MPM’s collection. The chosen objects include boxes, bowls, and other types of vessels. Through researching this collection, the following questions guided the direction for this thesis: How did the silver industry begin in Siam (Thailand) and how has it evolved throughout the years? How and why are certain decorative and symbolic motifs used on Thai silver vessels? Where did the motifs originate and how have they evolved? Through object analysis, the creation of an object biography and inventory (including photography), reaching out to institutions and anthropologists for additional information, and researching past and present changes to the industry, these methods helped to provide context and conclusions for the stated thesis questions. Silver from Thailand remains an elusive topic within both anthropology and art history lenses. The royal courts commissioned silversmiths to create exclusive goods in exchange for housing and all other necessities. Little is known about the history of the industry, gift giving practices, and purpose of the objects created. Each of the aesthetic motifs studied here provide different meanings for the objects, most of which pertain to fertility, wealth, health, or luck. Many of the objects provided different functions throughout their object lives, from useable items to keepsakes or status symbols. Others served exclusively religious functions. It is the aim of this paper to provide conclusions that will help to facilitate further knowledge and interest in the broader Thai silver history, industry, and practice.
Keywords: museum collection; royal; silver; silverware; Thailand